2017
DOI: 10.1186/s12872-017-0482-9
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and morbidity trends after the first year in survivors of acute myocardial infarction: a systematic review

Abstract: BackgroundMost studies of outcomes after myocardial infarction (MI) focus on the acute phase after the index event. We assessed mortality and morbidity trends after the first year in survivors of acute MI, by conducting a systematic literature review.MethodsLiterature searches were conducted in Embase, MEDLINE, and the Cochrane Database of Systematic Reviews to identify epidemiological studies of long-term (>10 years) mortality and morbidity trends in individuals who had experienced an acute MI more than 1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
1
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(177 citation statements)
references
References 33 publications
7
154
1
15
Order By: Relevance
“…The prevalence of comorbidities such as hypertension and diabetes, was high in the study population, and as shown in other studies, diabetes is a significant risk factor for recurrent events . In the Hoorn cohort study, the incidence of a recurrent cardiovascular event during approximately 4 years of follow‐up was 60% higher for individuals with diabetes compared with those without, and higher glycated hemoglobin was one of the predictive risk factors for a recurrent event .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The prevalence of comorbidities such as hypertension and diabetes, was high in the study population, and as shown in other studies, diabetes is a significant risk factor for recurrent events . In the Hoorn cohort study, the incidence of a recurrent cardiovascular event during approximately 4 years of follow‐up was 60% higher for individuals with diabetes compared with those without, and higher glycated hemoglobin was one of the predictive risk factors for a recurrent event .…”
Section: Discussionsupporting
confidence: 62%
“…In the Hoorn cohort study, the incidence of a recurrent cardiovascular event during approximately 4 years of follow‐up was 60% higher for individuals with diabetes compared with those without, and higher glycated hemoglobin was one of the predictive risk factors for a recurrent event . A recent systematic review of morbidity and mortality in patients who survived for at least 1 year following MI found that older age, history of stroke, and comorbidities, including diabetes, hypertension, peripheral artery disease, and renal disease, were associated with a greater risk of recurrent cardiovascular events or death …”
Section: Discussionmentioning
confidence: 99%
“…It is typically caused by the blockage of coronary artery, leading to the chest pain, weakness, diaphoresis, dyspnea, palpitation and even unconsciousness. The incidence of MI is declining in most countries with the development of therapeutic approaches [1]. However, the burden of MI is generally increasing as a result of the aging world population, population growth, and the rising prevalence of long-term survivors of MI [2].…”
Section: Introductionmentioning
confidence: 99%
“…21 In the case of MI, survivors are at high risk for death, or recurrent MI and other cardiovascular events. 25,26 Although, patient outcome is improving, there is considerable burden on healthcare systems and incidence is increasing in an aging and obese population.…”
Section: Future Perspectivesmentioning
confidence: 99%